2020
DOI: 10.3390/ijerph17197001
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depression, Anxiety and Stress and Their Associated Factors in College Students

Abstract: Aim: To estimate the prevalence of symptoms of depression, anxiety, stress and associated factors in a population of college students. Method: Cross-sectional study of psychological distress measured through the Depression, Anxiety and Stress Scale (DASS-21) in a sample of 1074 college students. Results: We found a moderate prevalence of depression (18.4%), anxiety (23.6%) and stress (34.5%) symptoms in our study population. Being <21, having problematic Internet use behavior, smoking, presenting insomnia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
178
6
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(289 citation statements)
references
References 57 publications
23
178
6
9
Order By: Relevance
“…Although studies have suggested that experiencing a severe infectious disease epidemic increases the prevalence of mental health issues, [12][13][14][15][16][17][18][19][20][21][22] it is difficult to find relevant literature or empirical studies that explore quarantine hotel employees faced with the challenge of psychological resilience. Therefore, this study aims to investigate the mental health status and psychological impact on quarantine hotel employees during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although studies have suggested that experiencing a severe infectious disease epidemic increases the prevalence of mental health issues, [12][13][14][15][16][17][18][19][20][21][22] it is difficult to find relevant literature or empirical studies that explore quarantine hotel employees faced with the challenge of psychological resilience. Therefore, this study aims to investigate the mental health status and psychological impact on quarantine hotel employees during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Each subscale contains seven items, and is scored using a 4-point Likert scale ranging from 0 (did not apply to me at all) to 3 (much or mostly applied to me). The depression subscale consists of questions 3, 5, 10, 13, 16, 17 and 21, and the score ranges are as follows: normal/no depression (0-9), mild depression (10-13), moderate depression (14)(15)(16)(17)(18)(19)(20), severe depression (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28 and above). The anxiety subscale consists of questions 2, 4, 7, 9, 15, 19, and 20, and the score ranges are as follows: normal/no anxiety (0-7), mild anxiety (8)(9), moderate anxiety (10)(11)(12)(13)(14), severe anxiety (15)(16)(17)(18)(19), and extremely severe anxiety (20 and above).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the prevalence of depression and anxiety in Spain is also high in comparison with other countries. For example, Ramón-Arbués et al, found a prevalence of depression of 18.4% and a prevalence of anxiety of 23.6% in Spanish adults, percentages that are higher than those found in adults in India (depression 12.1% and anxiety 19.0%) or in Brazilian adults (depression 14%) ( Sahoo and Khess, 2010 ; Silva et al, 2014 ; Ramón-Arbués et al, 2020 ).…”
Section: Introductionmentioning
confidence: 97%